Mapping inland wetlands in Africa using long waveband radar: the ALOS Kyoto and Carbon Initiative - Rebelo, Lisa-Maria (2009)
Throughout Sub-Saharan Africa, floodplains and wetlands are extensive. These ecosystems depend on frequent flooding. Many hydrological interventions either already exist within these basins, or are being planned to increase economic benefits and food security. However, these interventions will not be without consequences and both the costs and benefits need to be carefully evaluated. One likely consequence of increased flow regulation is reduced downstream flooding. The wetland ecosystems typically play a vital role in supporting rural populations and their sustainable management is thus critical. In order to prevent depletion of resources and ecosystem services provided by these wetlands, a balance is required between ecological and socio-economic factors. The sustainable management of wetlands requires information describing these ecosystems at multiple spatial and temporal scales. However, many African countries lack regional baseline information on the temporal extent, distribution and characteristics of wetlands. The ALOS Kyoto and Carbon Initiative is an international collaborative project led by the Japanese Aerospace Exploration Agency (JAXA) which has been set up to support the data and information needs posed by international environmental conventions, carbon cycle scientists; and environmental conservation programs. This paper reports on analysis planned under the Wetland Theme of this Initiative, for the Upper Nile Basin.